Performance evaluation of mechanical blossom thinning in Y-trellis pear orchard - Lei, Xiaohui; Lyu, Xiaolan; Zhang, Hongbin; Huang, Kai; Sun, Yuanhao; Ma, Zhengbao (International Journal of Agricultural and Biological Engineering, 2025)
As the largest fruit producer in the world, China’s comprehensive orchard mechanization rate is below 30% and faces the problem of aging orchard farmers. Thinning is an essential agronomic section in orchard management. Therefore, to get a marketable product, artificial hand fruit thinning (AHFT) has become a major but costly management practice in modern orchard planting. The authors developed two types of new orchard blossom thinners: tractor-mounted three-arm blossom thinner (TTBT) and hand-held electric blossom thinner (HEBT). The arm shape, spindle rotation speed, and rope arrangement density of TTBT can be adjusted flexibly according to the canopy structure of the fruit tree. HEBT is portable and suitable for different canopy types, especially for traditional orchard with complex-structured canopy. In this paper, a performance evaluation of the two types of blossom thinners on Y-trellis ‘Sucui’ No.1 pear orchard was carried out. In field tests, three treatments were designed and tested, which are TTBT combined with AHFT, HEBT combined with AHFT, and AHFT only. Four indices were used to evaluate the tests: blossom retention rate, fruit setting rate, fruit yield and quality, and work efficiency and cost. The test results showed that the blossom retention rate of TTBT and HEBT at 50% for Y-trellis ‘Sucui’ No.1 pear orchard was perfect; the difference of blossom retention rate and coefficient of variation of every layer of TTBT was very small, and the mean coefficient of variation was 2.97%, which is 1.98% lower than that of HEBT, meaning that the working stability of TTBT was higher than HEBT. The working efficiencies of TTBT and HEBT were much higher than that of AHFT, specifically, 130 and seven times higher, respectively. Although mechanical blossom thinning reduces the fruit setting rate to a certain extent, it has no effect on fruit yield and quality after fruit thinning for final marketable fruit. The profitable areas of TTBT and HEBT were 0.87 hm2 and 0.08 hm2, respectively. Keywords: agricultural machinery, mechanical blossom thinning, Y-trellis pear orchard, performance evaluation DOI: 10.25165/j.ijabe.20251804.9195Citation: Lei X H, Lyu X, Zhang H B, Huang K, Sun Y H, Ma Z B. Performance evaluation of mechanical blossom thinning in Y-trellis pear orchard. Int J Agric & Biol Eng, 2025; 18(4): 110–116.